Literasi Hukum Partai Politik, Pasca Putusan MK untuk Pilkada Inklusif Tegal - Widyastuti, Tiyas Vika; Aryani, Fajar Dian; Mahardika, Dinar; Pratama, Erwin Aditya; Sanusi , Sanusi (Nawadeepa: Jurnal Pengabdian Masyarakat, 2025)
Political parties hold a strategic position and serve as a primary pillar in Indonesia's democratic system, acting as a bridge between government policies and the aspirations of the people. However, personal-oligarchic leadership and an inadequate cadre system have resulted in party decision-making being frequently dominated by the interests of individual chairpersons, thereby threatening the future of democracy. An inclusive, transparent, and tiered cadre system is essential to uphold democratic principles in political recruitment and the nomination of public officials. The phenomena of factionalism and internal patronage within parties further exacerbate the political landscape, evidenced by conflict cases in several major parties. The process of electing regional heads, as a key component of democracy, is also influenced by the failures in recruitment. The Constitutional Court's Decision Number 60/PUU-XXII/2024 abolished the discriminatory nomination threshold for regional head candidates that previously disadvantaged smaller parties and independent candidates, thereby broadening opportunities for inclusive political participation. A community-based method is employed in community service within political parties in Tegal Regency to enhance legal literacy regarding this decision, involving party cadres and community leaders through workshops and interactive socialisation. This initiative aims to promote healthy and democratic political participation at the local level, strengthen inclusive democracy, and foster legal awareness among the populace. This study provides a comprehensive overview of the political dynamics and changes in the electoral system within the context of contemporary Indonesian democracy.